Réponses

Meilleure réponse !
2014-10-03T18:37:47+02:00
F(x) = (2x-1)(x+5-3) = (2x-1)(x+2) = 2x² + 3x - 2 
f(-1/3) = (-2/3-1)(-1/3+2) = -5/3 . 5/3 = -25/9
f(√2) = 2(√2)² + 3√2 - 2 = 4 - 2 + 3√2 = 2  + 3√2

2014-10-03T18:40:23+02:00
1.f(-1/3)=(2x-1)(x+5)-3(2x-1)
            = (2*-1/3-1)(-1/3+5)-3(2*-1/3-1)
             = (-2/3-1)(-1/3+5)-3(-2/3-1)
               = 2/9-10/3+1/3-5+6/3+3
                 = 2/9-9/9-18/9
                 = 2/9-9/9-18/9
                 = 2/9-27/9
                 = -25/9
Pour le 2. c'est le même principe, tu remplace le x par racine carré de 2 !
Bon courage pour la suite !! :)